Edible flowers: restorers of five senses - Sumalatha, Akkalareddy; Mallesh, Sanganamoni; Hiremat, Varun (Indian Horticulture, 2019)
Edible flowers are flowers that are used as a garnish or as an integral part of a dish, such as a salad. There is an increased demand for fresh and good quality flowers for human consumption worldwide because of their taste, colour, fragrance and nutraceutical properties. Many flowers are edible and the flowers of most culinary herbs are safe. Using flowers as a part of cookery enhances the aesthetic appearance of food and increase the appetite by providing colour, taste, aroma and flavour. Now-a-days, nutraceuticals are receiving considerable interest because of their presumed safety, and potential nutritional and therapeutic effect. Flowers, as a natural resource, have been attracting more and more attention owing to their great potential values of natural antioxidants and scavenging activity of reactive oxygen radicals acts as anticancer agents. Flowers, are packed full of vitamins and minerals (Ex. Rose petals contain Vitamin C). However, proper identification is essential because some flowers are poisonous and should not be eaten.